Social Protection and Jobs Responses to COVID-19 : A Real-Time Review of Country Measures - Gentilini,Ugo; Almenfi,Mohamed Bubaker Alsafi; Iyengar,TMM; Okamura,Yuko; Downes,John Austin; Dale,Pamela; Weber,Michael; Newhouse,David Locke; Rodriguez Alas,Claudia P; Kamran,Mareeha; Mujica Canas,Ingrid Veronica; Fontenez,Maria Belen; et al. (Washington, DC: World Bank, 2022)
As of January 2022, a total of 3,856 social protection and labor measures were planned or implemented by 223 economies. This constitutes a net increase of 523 measures, or 15.6 percent since the last update in May 2021. While noteworthy, such increase is the lowest among net additions observed over previous semesters. In fact, the global pace of measures’ introduction over January 2020-January 2022 has been slowing down. This report focuses on the real-time review of country measures in terms of social protection and job responses to Coronavirus (COVID-19).